mRNA-based COVID-19 Vaccines Booster Dose: Benefits, Risks and Coverage: COVID-19 Vaccines Booster Dose - Nashwan, Abdulqadir; Yassin, Mohamed; Soliman, Ashraf; De Sanctis, Vincenzo; Ibrahim, Mohamed (Acta Biomedica Atenei Parmensis, 2022)
The number of COVID-19 vaccine-rich countries that have started COVID-19 third-dose booster programs is growing dramatically despite the lack of robust evidence on the effectiveness, safety, and frequency of the required booster doses that makes the individuals/populations immune to COVID -19 infection. Beyond the ethical dilemma, the scarcity of studies on the optimal timing for offering booster doses, eligibility criteria, and if there is any association between premature or delayed administration and the degree of protection against infection. The aim of this mini- review was to collect and analyze published data on this topic in a trial to answer some questions related to the benefits versus the risks of offering frequent boosters of mRNA vaccines for increasing the population immunity against COVID-19 infection considering the current policy of providing SARS-CoV-2 vaccine booster doses in rich countries versus those in relatively poor countries with limited access to vaccination. (www.actabiomedica.it)